Design and Implementation of Automotive Sunlight Curtain for Cars Using Digital Electronic Circuit (Al-Mansour Journal, 2022)
In this paper, a novel technique of an automotive electromechanical sunlight curtain for the cars is designed and implemented. It depends on applying the sunlight rays on a photodiode at an angle fitted to that of the sunlight rays falling on the eyes of the car driver and the person beside him and make them uncomfortable. The proposed system is composed from four main parts: The photodiode and related comparator, a control circuit, 12 Volt DC motor with gearbox, and sunlight curtain plate with some mechanical parts. When the sunlight rays fall onto the photodiode with an desired angle, the control circuit will instruct the DC motor to rotate in clockwise direction, the motor will rotate the curtain plate to the downside location, where the curtain plate will prevent the sunlight rays to fall on eyes of the car driver or the person beside him. The proposed system has been tested practically in different environment conditions and different seasons, and it has exhibited stimulant results.
Keywords: Comparators; Flip-flop; One-shot-to; Photodiode; Sunlight Curtain